Effectiveness of Once-Weekly Rifapentine and Moxifloxacin Regimens against Mycobacterium tuberculosis in Mice - Lounis, Nacer (American Society for Microbiology, 2001)
Mice infected with 1.6 × 10(7) CFU of Mycobacterium tuberculosis were treated 14 days later for 6 months with a regimen of once-weekly 10 mg of rifapentine and 75 mg of isoniazid per kg of body weight supplemented with either 150 mg of streptomycin per kg or 100 mg of moxifloxacin per kg during either both the 2-week daily initial and once-weekly continuation phases or only in the daily 2-week initial phase. On completion of treatment, all lung cultures were negative, except for three mice, each with a single colony: two whose rifapentine-isoniazid regimen was supplemented with streptomycin during the whole course of therapy and one whose rifapentine-isoniazid regimen had no initial daily phase, but was supplemented with streptomycin and moxifloxacin during the whole course of therapy. After 3 months of follow-up, positive lung cultures were obtained from 61 and 56% of mice supplemented with streptomycin during either the full course of therapy or only the daily 2-week initial phase, respectively, and 15 and 50% of mice supplemented with moxifloxacin during either the full course of therapy or only the daily 2-week initial phase, respectively. These results suggest that moxifloxacin has sterilizing activity against M. tuberculosis.